Cost of Production for Processed Oranges Grown in Southwest Florida, 2015/16 - Ariel Singerman (EDIS)
This article presents a summary of the 2015/16 costs of production for Processed Oranges in Southwest Florida. The methodology chosen to collect the data consisted of surveying growers directly to closely reflect growers’ costs in the era of HLB. The total cost of production for Processed Oranges in 2015/16 was $2,327.98 per acre, down $87.86 per acre from last season.